2019
DOI: 10.3390/electronics8060653
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Model to Evaluate the Effects of High Level C++ Code Hardening in Radiation Environments

Abstract: A high-level C++ hardening library is designed for the protection of critical software against the harmful effects of radiation environments that can damage systems. A mathematical and empirical model to predict system behavior in the presence of radiation induced faults is also presented. This model generates a quick evaluation and adjustment of several reliability vs. performance trade-offs, to optimize radiation hardening based on the proposed C++ hardening library. Several simulations and irradiation campa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This was implemented on a zynq-7000 development board (Zybo) and it was shown that the proposed method could be used for a radiation tolerant synchronous buck converter design for applications requiring a relatively longer mission time, compared to the TMR and FMR techniques. In [13], a compact model was presented to evaluate the effects of high-level C++ code radiation hardening. The use of appropriate C++ classes facilitated the use of TMR.…”
Section: The Present Issuementioning
confidence: 99%
“…This was implemented on a zynq-7000 development board (Zybo) and it was shown that the proposed method could be used for a radiation tolerant synchronous buck converter design for applications requiring a relatively longer mission time, compared to the TMR and FMR techniques. In [13], a compact model was presented to evaluate the effects of high-level C++ code radiation hardening. The use of appropriate C++ classes facilitated the use of TMR.…”
Section: The Present Issuementioning
confidence: 99%
“…To evaluate the hardening performance and estimate the inherent trade-offs between speed, memory footprint and fault coverage, a compact mathematical model presented in [26] has been used. This model evaluates the effects of high-level C++ code hardening.…”
Section: Resultsmentioning
confidence: 99%
“…Time-Size and MWTF metrics are showed in Table 2, where better applications are considered those with higher reliability and lower execution time (lower χ and higher MWTF). As in the cited paper [26], the proposed model was evaluated against real radiation measurements with protons and neutrons during two radiation campaigns described in it. As can be seen, the reference version presents a MWTF of 1.21 in protons and 0.35 in neutrons, which is only improved by TMR versions.…”
Section: Resultsmentioning
confidence: 99%
“…• HData (H) [17] -Hardened Data: classes templates on C++ that replace the basic language types, in order to implement automated and transparent TMR protection. Benchmarks were coded using the following name convention: first the benchmark name, then the hardening technique applied, and finally the version number.…”
Section: Benchmarksmentioning
confidence: 99%
“…A preliminary work was presented in [17] that focused on optimizing the application of a High Level SIHFT technique to a reduced number of programs. This work extends that effort in two ways: 1) characterizing two platforms (ARM and MSP430) using the parameters obtained from the trained models; and, 2) analyzing and optimizing the application of three different SIHFT techniques to the benchmark suite: lowlevel implemented, high-level implemented and non-intrusive.…”
Section: Introductionmentioning
confidence: 99%